Effects of Temperature and Carrier Gas on Phosphorus Transformation in Biosolids Biochar - Shefali Aktar; Md Afzal Hossain; Gabriel Gasco; Ana Mendez; Cicero Celio de Figueiredo; Kalpit Shah; Jorge Paz-Ferreiro (Land)
Phosphorus (P) is an essential macronutrient for plants. The focus of this work is to recover P from biosolids and their derived biochar. The effect of three different pyrolysis temperatures (400 °C, 500 °C, and 600 °C) and two carrier gases (CO2 and N2) on P fractionation and the speciation of P on biochars produced from two biosolids were investigated. The Hedley chemical sequential extraction method and 31P liquid NMR were used for P characterization and quantification. Higher pyrolysis temperatures increased P fixation and decreased short-term P bioavailability. Carrier gas had also significant effects on P fractionation in the biochars. Biochar produced in a CO2 environment had slightly higher water-soluble P, NaHCO3-Pi, NaOH-Pi, and residual P than in biochar prepared in a N2 environment, while HCl-P showed the opposite trend. Additionally, the predominant molecular configuration of P was present in the inorganic form identified by 31P liquid NMR spectra, while organic P transformed into inorganic P with increasing pyrolysis temperature.